The Process of Making Nata de Salacca from Honey Salak Fruit (Salacca edulis Reinw) with the Application of Biotechnology Techniques - Irwani, Anisa Novia; Auranina Oskandar, Yasmin; Novia Irwani, Anisa; Putri Rahmawati, Dian; Puri Ducha Rahmani, Tara (Universitas Ahmad Dahlan, 2021)
Salak is typical Indonesian fruit commonly found in tropical countries. This fruit can fill global fruit market via exports to various countries. One of the varieties is